Factors impacting the benefits and pathogenicity of Th17 cells in the tumor microenvironment - Xing, Jie; Man, Changfeng; Liu, Yingzhao; Zhang, Zhengdong; Peng, Huiyong (Frontiers in Immunology, 2023)
Tumor development is closely associated with a complex tumor microenvironment, which is composed of tumor cells, blood vessels, tumor stromal cells, infiltrating immune cells, and associated effector molecules. T helper type 17 (Th17) cells, which are a subset of CD4 + T cells and are renowned for their ability to combat bacterial and fungal infections and mediate inflammatory responses, exhibit context-dependent effector functions. Within the tumor microenvironment, different molecular signals regulate the proliferation, differentiation, metabolic reprogramming, and phenotypic conversion of Th17 cells. Consequently, Th17 cells exert dual effects on tumor progression and can promote or inhibit tumor growth. This review aimed to investigate the impact of various alterations in the tumor microenvironment on the antitumor and protumor effects of Th17 cells to provide valuable clues for the exploration of additional tumor immunotherapy strategies.